Oncologic safety of cervical nerve preservation in neck dissection for head and neck cancer. Issue 9 (30th May 2017) - Honda, Keigo; Asato, Ryo; Tsuji, Jun; Miyazaki, Masakazu; Kada, Shinpei; Tsujimura, Takashi; Kataoka, Michiko
Abstract: Background: Although the functional merits of preserving cervical nerves in neck dissection for head and neck cancer have been reported, the oncologic safety has not yet been determined. Therefore, the purpose of this study was to evaluate the safety of cervical nerve preservation. Methods: A retrospective chart review was performed on patients with head and neck cancer who had been treated by neck dissection between 2009 and 2014 at Kyoto Medical Center. Management of cervical nerves and clinical results were analyzed. Results: A total of 335 sides of neck dissection had been performed in 222 patients. Cervical nerves were preserved in 175 neck sides and resected in 160 sides. The 5‐year overall survival (OS) rate calculated by the Kaplan‐Meier method was 71%. The 5‐year neck control rate was 95% in cervical nerve preserved sides and 89% in cervical nerve resected sides. Conclusion: Preserving cervical nerves in neck dissection is oncologically safe in selected cases.